Pengelolaan Sumber Daya Insani dalam Memasarkan Produk dan Jasa Lembaga Keuagan Syariah - Rahma Sari Zein (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Human resource administration in Islamic financial institutions' marketing of their goods and services is the subject of this study. The study's findings demonstrate the rapid growth of Indonesia's Islamic financial institutions. However, Islamic financial institutions and banks have a poor reputation in Indonesia. As a result, a number of management policies for Islamic financial institutions must be addressed. The human resources aspect is one of them. An employee of an accepted bank or Islamic financial institution must possess a positive personality, be knowledgeable about Islamic financial institutions, computers, and other topics, and be an expert in muqalah fiqh. They need to be people who strongly support putting Islamic economics into practice throughout their lives.